Gender features of perception of information in a family - Bilyk О.; Lytvinenko О. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2014)
The process of text perception fundamentally depends on the sex of the recipient. The prehension of information by men and women is sometimes diametrically opposed. This is one of the main reasons of the family communication barrier’s appearance, which, in it’s turn, threatens the harmonious development of the family. This article describes the main obstacle encountered in communication partners due to sex differences. And also the possible ways of elimination of the interference.